Quad Band Notched MIMO Antenna for Portable UWB Applications - Dr. B. Premalatha, G. Srikanth (International Journal of Advanced Science and Technology, 2020)
Circular UWB MIMO antenna with CPW feeding is proposed in this paper. This paper mainly focuses on the design, simulation, fabrication & testing of a MIMO antenna with band dispensation characteristics which is useful for UWB applications. UWB is a very promising technology for short-range wireless communications provides high data rate communication in the frequency band of 3.1-10.6GHz for unlicensed applications. To avoid interference between UWB and existing wireless communication systems, band notching characteristics are proposed. This paper mainly focuses on the elimination of interference with the existing wireless bands like Wi-MAX, WLAN, X- Band Satellite Communication System and ITU band for radio-frequency channel arrangements for fixed wireless systems. To achieve the required band dispensation annular rings with rectangular split bricks are placed on the patch. The MIMO antenna is designed and simulated using CST microwave studio software and the antenna parameters like Return losses (S11), Gain, VSWR, Radiation patterns, Correlation Coefficient, Gain are measured. The simulated antenna is fabricated using RT/ Duroid 5880 substrate material with a height 1.57mm. The simulated and measured results are compared and reported.